2015
DOI: 10.1371/journal.pone.0122402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild-to-Moderate Smoking on Viral Load, Cytokines, Oxidative Stress, and Cytochrome P450 Enzymes in HIV-Infected Individuals

Abstract: Mild-to-moderate tobacco smoking is highly prevalent in HIV-infected individuals, and is known to exacerbate HIV pathogenesis. The objective of this study was to determine the specific effects of mild-to-moderate smoking on viral load, cytokine production, and oxidative stress and cytochrome P450 (CYP) pathways in HIV-infected individuals who have not yet received antiretroviral therapy (ART). Thirty-two human subjects were recruited and assigned to four different cohorts as follows: a) HIV negative non-smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 54 publications
14
80
0
Order By: Relevance
“…Upon reaching the U1 cells, these EVs release CYPs into the cytosol, where they induce oxidative stress and subsequently HIV-1 replication. Our observations are in agreement with our previous reports, where we observed a higher expression of CYPs, oxidative stress, and HIV-1 viral load in the plasma samples of HIV-1 smokers, which shows the association of a CYP-mediated oxidative stress pathway in HIV-1 replication [55]. Recently, we confirmed this association in vitro in U1 cells, in which we demonstrated that CYP1A1 metabolizes benzo(a)pyrene (a harmful carcinogen in cigarette smoke) and causes increased production of ROS, which subsequently triggers HIV-1 replication in the U1 cells [23].…”
Section: Discussionsupporting
confidence: 94%
“…Upon reaching the U1 cells, these EVs release CYPs into the cytosol, where they induce oxidative stress and subsequently HIV-1 replication. Our observations are in agreement with our previous reports, where we observed a higher expression of CYPs, oxidative stress, and HIV-1 viral load in the plasma samples of HIV-1 smokers, which shows the association of a CYP-mediated oxidative stress pathway in HIV-1 replication [55]. Recently, we confirmed this association in vitro in U1 cells, in which we demonstrated that CYP1A1 metabolizes benzo(a)pyrene (a harmful carcinogen in cigarette smoke) and causes increased production of ROS, which subsequently triggers HIV-1 replication in the U1 cells [23].…”
Section: Discussionsupporting
confidence: 94%
“…Plasma was prepared as described earlier [13] from human blood samples of unidentified healthy individuals, which were obtained from Interstate Blood Inc. (Memphis, TN). Exosomes were isolated first by filtering plasma (200 – 500 μl) through a 0.22 micron filter to remove large vesicles (>200 nm) followed by using Plasma Exo Kit (Applied Biosystems, Foster City CA).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative reverse transcription polymerase chain reaction (RT‐PCR) was performed as described in our previous studies (Ande et al., 2015a). Briefly, 120 ng of RNA was reverse transcribed to cDNA and then amplified in the StepOnePlus system from Life Technologies using a 2‐step TaqMan Gene Expression Kit (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…In the past 5 years we have utilized U937 cell lines and primary M/M to study the acute effects of alcohol and tobacco constituents. Recently, we have demonstrated relatively high expressions of CYP2E1 and CYP3A4 in U937 monocytic cell lines (Jin et al., ) and primary M/M (Ande et al., 2015a). Importantly, we have also demonstrated significant induction of these CYP enzymes by acute exposure to EtOH and increase in oxidative stress in U937 cells (Jin et al., , ).…”
mentioning
confidence: 99%